1994
DOI: 10.1104/pp.106.2.673
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Mutation Inhibits Expression of the Chloroplast Gene That Encodes the Large Subunit of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase

Abstract: Chlamydomonas reinhardtii mutant 76-SEN was recovered as a light-sensitive, acetate-requiring strain that failed to complement a chloroplast structural gene mutant of ribulose-l,5-bisphosphate carboxylase/oxygenase (Rubisco; EC 4.1.1.39). Further genetic analysis revealed that the new mutation was inherited in a mendelian pattern, indicating that it resides within the nucleus. The 76-5EN mutant lacks Rubisco holoenzyme but has wild-type levels of whole-chain electron transport activity and chlorophyll. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…It has been proposed that reduced chloroplast gene expression during leaf senescence results from decreased chloroplast function followed by increased chloroplast breakdown (Camp et al, 1982;Mae et al, 1984;Wardley et al, 1984;Ford and Shibles, 1988;Kura-Hotta et al, 1990). In RbcS antisense-inhibited transgenic tobacco, the developmental reduction of rbcL transcripts observed in older leaves has been correlated with a decrease in plastid DNA template availability (Jiang and Rodermel, 1995). In a similar fashion, the reduction in rbcL mRNA levels at the ' tips of bsd2-ml light-grown leaves could be a consequence of chloroplast breakdown.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been proposed that reduced chloroplast gene expression during leaf senescence results from decreased chloroplast function followed by increased chloroplast breakdown (Camp et al, 1982;Mae et al, 1984;Wardley et al, 1984;Ford and Shibles, 1988;Kura-Hotta et al, 1990). In RbcS antisense-inhibited transgenic tobacco, the developmental reduction of rbcL transcripts observed in older leaves has been correlated with a decrease in plastid DNA template availability (Jiang and Rodermel, 1995). In a similar fashion, the reduction in rbcL mRNA levels at the ' tips of bsd2-ml light-grown leaves could be a consequence of chloroplast breakdown.…”
Section: Discussionmentioning
confidence: 67%
“…For example, a point mutation in the tobacco rbcL gene that prevents holoenzyme assembly results in a 98% reduction in steady state levels of both large and small subunit proteins (Avni et al, 1989). Similarly, antisense inhibition of RbcS gene expression in transgenic tobacco prevents large subunit protein accumulation, although rbcL transcripts accumulate to normal levels and are translated (Rodermel et al, 1988;Jiang and Rodermel, 1995). ln bsd2-ml leaves, RbcS transcript accumulation profiles were essentially normal; however, the spatial and temporal regulation of rbcL transcripts was disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…When the acetaterequiring insertional mutants were screened by SDS͞PAGE and Western blot analysis, one of the light-sensitive strains, named T60-3, was found to lack Rubisco large and small subunits. This is a common attribute of a number of Rubisco mutants that have primary defects in large-subunit synthesis or assembly (5,6,31,36). However, 35 SO 4 2Ϫ -labeling experiments indicated that little or no synthesis of either subunit occurred during a 1-min pulse (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the DNA integrates into the nuclear genome at apparently random loci, the transforming DNA can act as an insertional mutagen to disrupt functional genes (37,38). We initially decided to use this method to physically mark alleles of mutant nuclear genes that affect Rubisco expression, stability, and catalysis (28,36,39). A dark-grown cw d arg-7-8 mt Ϫ strain, which lacks a cell wall and requires arginine for growth (26), was transformed with plasmid pARG7.8, which contains the wild-type argininosuccinate lyase gene (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation